Influence of temperature on the progamic phase in Citrus - Montalt, Rafael; Cuenca, José; Vives, María C.; Navarro, Luis; Ollitrault, Patrick; Aleza, Pablo (2020)
Temperature in the progamic phase is critical for the success of plant sexual reproduction, and new knowledge is needed to optimise breeding programmes to obtain new varieties that adapt to a climate change scenario. Using three male donors and one female recipient in the genus Citrus, we evaluated the effect of four temperature regimes on each process in the progamic phase. An innovative method based on microscopic observations of cross sections from pollinated pistils collected daily allowed a comprehensive analysis of pollen tube growth (dynamics and kinetics) along the pistil. Pollen grain germination and stigmatic receptivity were evaluated directly on the stigma, which offers more accurate information than previously reported in vitro experiments. Our results showed that warm temperatures reduce the time needed by pollen tubes to reach ovules and accelerate pistil degeneration, while cold temperatures produce the opposite effects. Interestingly, we observed both pollen grain germination and pollen tube growth at 10 degrees C, which have not been observed in previous studies in citrus. At this temperature, the differences observed in both pollen grain germination and pollen tube growth for different genotypes reflect the adaptation of their sporophytic generation to low temperatures which would enable gametophytic screening to be used as a tool to select better adapted genotypes to different temperature conditions. The differences observed in the growth rates between pollen tubes in each genotype-temperature combination provide an opportunity to explore additional gametophytic selection in this reproductive phase. The capacity to respond to temperature changes in the progamic phase to ensure mating can be useful for breeding programs that focus on obtaining better adapted populations to different temperature conditions.